Probabilistic seismic hazard map analysis for Aceh Tenggara district and microzonation for Kutacane city. Issue 1 (January 2021) - Irwandi, I.; Muksin, Umar; Asrillah,; Simanjuntak, Andrean V H; Asrurifak,
Abstract: The Aceh Tenggara (Southeast Aceh) District, especially Kutacane, is located along with the main GSF (Great Sumatra Fault) system and the Tripa segment in particular based on seismic hazard map of Indonesia 2017. Therefore, the seismic hazard map needs to be updated based on the recent seismotectonic information and the latest active fault investigations. This paper discusses the updated seismic hazard map for the Aceh Tenggara district. In seismic hazard calculation, input source definition including fault characteristics, subduction zone, and seismicity background. Ground Motion Prediction Equation (GMPE) is used by the Indonesian official seismic hazard map 2017 to compute the hazard curve of strong ground shaking. Probability exceeding 2% and 10% for 50 years is chosen to calculate PGA (Peak Ground Acceleration) map on bedrock. On the other hand, Kutacane is located on a younger alluvium basin in the Holocene epoch thus site sediment amplification effect is taken into account in the microzonation calculations (local scale). The geomorphological slope is used to estimate the Vs30 distribution map. The site amplification is calculated based on PGA value on bedrock and Vs30 value on each site location. The Probabilistic Seismic Hazard Analysis (PSHA) is applied to produce seismic hazard maps as also used since many scientists and engineers in Indonesia although for critical infrastructure Neo-Deterministic Seismic Hazard Analysis (NDSHA) is suggested to be applied. The newly updated seismic hazard map can be used for the reference of infrastructure development in order to reduce the risk of disaster.